The efficacy and safety of warming acupuncture and moxibustion on rheumatoid arthritis: A protocol for a systematic review and meta-analysis. Issue 34 (21st August 2020) - Shang, Jingwen; Fan, Wei; Dou, Zhongqing; Wu, Linlin; Lu, Bibo; Qian, Junhui
Abstract: Background: Rheumatoid arthritis (RA), as an autoimmune disease, can eventually lead to joint deformity and loss of function, seriously reduce the quality of life of patients and increase economic burden. As a traditional Chinese therapy, warming acupuncture and moxibustion is safe, economical, and has few side effects. At present, some studies have shown that warming acupuncture and moxibustion has a certain effect on RA, but there is no evidence of evidence-based medicine. The purpose of this study was to evaluate the efficacy and safety of warming acupuncture and moxibustion in the treatment of rheumatoid arthritis. Method: Randomized controlled trials of warming acupuncture and moxibustion treating RA will be searched in the databases including PubMed, EMBASE, the Cochrane library, Web of science, China National Knowledge Infrastructure (CNKI), WanFang, the Chongqing VIP Chinese Science and Technology Periodical Database (VIP), and China biomedical literature database (CBM) from inception to July, 2020. In addition, Baidu, Google Scholar, International Clinical Trials Registry Platform, and Chinese Clinical Trials Registry will be searched to obtain the gray literature and relevant data that have not yet been published. Two qualified researchers will extract data and assess the risk of bias from included studies independently. Statistical analysis is performed in RevMan 5.3 software. Results: The primary outcome is symptom evaluation including morning stiffness, pain, and joint swelling. The number of joints affected by RA, Rheumatoid factor (RF), erythrocyte sedimentation rate (ESR), C reactive protein (CRP), anti-cyclic peptide containing citrulline (A-CCP), and adverse effects, will be evaluated as secondary outcomes. Conclusions: This study will compare the efficacy and safety of warming acupuncture and moxibustion with common acupuncture in the treatment of RA, providing reliable evidence for clinical application. OSF Registration number: DOI 10.17605/OSF.IO/C8RY9.